An Overview Of Matched Bandstop Filters Using Lossy Resonators - Noor Azwan, Shairi; Ahmad, Badrul Hisham; Zakaria, Zahriladha; Wong, Peng Wen (AENSI, 2014)
The overview of theory, design, development and application of matched bandstop filters using lossy resonators are presented in this paper. Theoretically, high notch depth and selectivity of matched bandstop filters can be produced by using only two lossy low Q resonators. Many matched bandstop filters have been developed during the last few years where the main targeted applications are advanced communication and electronic warfare systems. This article is mainly to provide the readers with some basic knowledge and insights about previous works of the matched bandstop filters using lossy resonators